A Cam Morphology Develops in the Early Phase of the Final Growth Spurt in Adolescent Ice Hockey Players: Results of a Prospective MRI-based Study. Issue 5 (May 2021) - Hanke, Markus S.; Schmaranzer, Florian; Steppacher, Simon D.; Reichenbach, Stephan; Werlen, Stefan F.; Siebenrock, Klaus A.
Abstract: Background: Cam morphologies seem to develop with an increased prevalence in adolescent boys performing high-impact sports. The crucial question is at what age the cam morphology actually develops and whether there is an association with an aberration of the shape of the growth plate at the cam morphology site. Questions/purposes: (1) What is the frequency of cam morphologies in adolescent ice hockey players, and when do they appear? (2) Is there an association between an extension of the physeal growth plate and the development of a cam morphology? (3) How often do these players demonstrate clinical findings like pain and lack of internal rotation? Methods: A prospective, longitudinal MRI study was done to monitor the proximal femoral development and to define the appearance of cam morphologies in adolescent ice hockey players during the final growth spurt. Young ice hockey players from the local boys' league up to the age of 13 years (mean age 12 ± 0.5 years) were invited to participate. From 35 players performing on the highest national level, 25 boys and their parents consented to participate. None of these 25 players had to be excluded for known disease or previous surgery or hip trauma. At baseline examination as well as 1.5 and 3 years later, we performed a prospective noncontrast MRI scan and a clinical examination. The three-dimensional morphology of the proximal femur was assessed by one of the authors using radial images of the hip in a clockwise manner. The two validated parameters were: (1) the alpha angle for head asphericity (abnormal > 60°) and (2) the epiphyseal extension for detecting an abnormality in the shape of the capital physis and a potential correlation at the site of the cam morphology. The clinical examination was performed by one of the authors evaluating (1) internal rotation in 90° of hip and knee flexion and (2) hip pain during the anterior impingement test. Results: Cam morphologies were most apparent at the 1.5-year follow-up interval (10 of 25; baseline versus 1.5-year follow-up: p = 0.007) and a few more occurred between 1.5 and 3 years (12 of 23; 1.5-year versus 3-year follow-up: p = 0.14). At 3-year follow-up, there was a positive correlation between increased epiphyseal extension and a high alpha angle at the anterosuperior quadrant (1 o'clock to 3 o'clock) (Spearman correlation coefficient = 0.341; p < 0.003). The prevalence of pain on the impingement test and/or restricted internal rotation less than 20° increased most between 1.5-year (1 of 25) and the 3-year follow-up (6 of 22; 1.5-year versus 3-year follow-up: p = 0.02). Conclusion: Our data suggest that a cam morphology develops early during the final growth spurt of the femoral head in adolescent ice hockey players predominantly between 13 to 16 years of age. A correlation between an increased extension of the growth plate and an increased alpha angle at the site of the cam morphology suggests a potential underlying growth disturbance. This should be further followed by high-resolution or biochemical MRI methods. Considering the high number of cam morphologies that correlated with abnormal clinical findings, we propose that adolescents performing high-impact sports should be screened for signs of cam impingement, such as by asking about hip pain and/or examining the patient for limited internal hip rotation. Level of Evidence: Level I, prognostic study.